Test results of fault current limiter using YBCO tapes with shunt protection - Baldan, Carlos A. [UNESP]; Lamas, Jérika S.; Shigue, Carlos Y.; Filho, Ernesto Ruppert (IOP Publishing, 2010)
A Fault Current Limiter (FCL) based on high temperature superconducting elements with four tapes in parallel were designed and tested in 220 V line for a fault current peak between 1 kA to 4 kA. The elements employed second generation (2G) HTS tapes of YBCO coated conductor with stainless steel reinforcement. The tapes were electrically connected in parallel with effective length of 0.4 m per element (16 elements connected in series) constituting a single-phase unit. The FCL performance was evaluated through over-current tests and its recovery characteristics under load current were analyzed using optimized value of the shunt protection. The projected limiting ratio achieved a factor higher than 4 during fault of 5 cycles without degradation. Construction details and further test results will be shown in the paper. © 2010 IOP Publishing Ltd.
Keywords: Effective length; Fault currents; Fault-current limiter; High temperature superconducting; HTS tapes; Load currents; Over current; Second generation (2G); Stainless steel reinforcement; Test results; YBCO coated conductors; YBCO tape; Critical current density (superconductivity); Electric fault currents; High temperature superconductors; Limiters; Stainless steel; Superconductivity; Yttrium barium copper oxides; Superconducting tapes